In vitro antiprotozoal activity and cytotoxicity of extracts and fractions from the leaves, root bark and stem bark of Isolona hexaloba. (4th November 2015) - Musuyu Muganza, D.; Fruth, B.I.; Nzunzu Lami, J.; Cos, P.; Cimanga Kanyanga, R.; Maes, L.; Pieters, L.
Abstract: Ethnopharmacological relevance: Isolona hexaloba (Pierre) Engl. and Diels (Annonaceae) is traditionally used in D.R. Congo against parasitic diseases including malaria. Materials and methods: Two crude aqueous extracts, 3 crude methanol extracts and 3 crude 80% ethanol extracts from the leaves, root bark and stem bark together with 12 subfractions from the crude 80% ethanol extracts were evaluated in vitro for their antiprotozoal activity against Trypanosoma brucei brucei, T. cruzi, Leishmania infantum and the chloroquine and pyrimethamine resistant K1 strain of Plasmodium falciparum. Their cytotoxic effects against MRC-5 cell lines were also assessed. Results: Results indicated that the most pronounced activities against T. b. brucei were recorded for the crude methanol extracts of root bark (IC50=1.97 µg/ml; SI>32.49) and leaves (IC50=2.65 µg/ml; SI>24.15). Three samples displayed good activity against T. cruzi: the 80% methanol extract of leaves (IC50=8.33 µg/ml; SI>3.92), its petroleum ether fraction (IC50=8.50 µg/ml; SI=2.52) and the crude aqueous extract of the stem bark (IC50=9.31 µg/ml; SI=3.46). The crude aqueous extract of the leaves exhibited a pronounced and selective activity against L. infantum (IC50=2.00 µg/ml; SI>32). The crude methanol extract of leaves (IC50=6.35 µg/ml; SI>10.10) and the 2 dichloromethane soluble fractions of the 80% ethanol extracts from root bark (IC50=6.96 µg/ml; SI=6.1) and stem bark (IC50=8 µg/ml; SI>8.00) showed good activity and selectivity against L. infantum . The most active samples against Plasmodium falciparum K1 were the leaves crude 80% ethanol extract (0.92 µg/ml) and its fractions: alkaline aqueous (IC50=0.27 µg/ml), 90% methanol (0.90 µg/ml) and dichloromethane (1.04 µg/ml), respectively, with promising selectivity indexes of 35<SI<237. None of all the tested crude extracts and fractions was found to be cytotoxic against MRC-5 cell lines except the petroleum ether soluble fraction from the leaves which displayed a cytotoxic effect (CC50=21.40 µg/ml). Conclusion: Overall, extracts of I. hexaloba tested here, showed good results concerning parasitic infections such as Chagas' disease, leishmaniasis, malaria and/or sleeping sickness without considerable toxicity. The 80% ethanol extracts from leaves and their fractions turned out to be of special interest as they were the most useful in the treatment of malaria. Graphical abstract: